Assessment of Clinical and Laboratory Variables as a Guide to Packed Red Blood Cell Transfusion of Euvolemic Anemic Dogs. (13th January 2014) - Kisielewicz, C.; Self, I.; Bell, R.
<x xml:space="preserve">Abstract</x> Background There are no standardized guidelines for determining the likelihood that euvolemic anemic dogs will benefit from transfusion of packed red blood cells (pRBC). Objectives To report clinical and laboratory variables of dogs receiving pRBC transfusion, which could guide transfusion of other anemic dogs. Animals Twenty‐four client‐owned anemic dogs receiving pRBC transfusion. Methods Prospective study; 30 transfusions assessed. Clinical findings (mucosal color, pulse quality, heart rate, respiratory rate, mentation/exercise tolerance) before and after transfusion were evaluated by the anemic dog clinical assessment score (ADCAS). Hemoglobin concentration, hematocrit, venous oxygen content (CvO2), and lactate concentration were measured from blood samples taken before and after transfusion. These results were not used for case management. Results All ADCAS variables decreased significantly with transfusion (P < .001); the total score was ≥5/12 before transfusion, and ≤3/12 in all cases that were deemed to no longer require transfusion. Hematocrit and CvO2 were <17% and <5 mL/dL, respectively, in 83% of cases before transfusion and hemoglobin concentration was <5.8 g/dL in 80%. Hemoglobin concentration, hematocrit, and CvO2 increased significantly with transfusion (P < .001); lactate concentration decreased significantly (P = .006). Conclusions and Clinical Importance Clinical and laboratory variables improved significantly after transfusion of pRBC. By identifying how transfusion affected these variables, it was possible to recognize clinical (ADCAS) and laboratory (hemoglobin, CvO2, lactate) variables, which could be useful in guiding the decision to transfuse dogs with similar presentations.